Stereotypes and Gender Roles in Pandey’s Jiyara: Changing the Script - Bista, Asmita (Mindscape: A Journal of English & Cultural Studies, 2023)
Nayan Raj Pandey’s Jiyara, an anthology of stories, portrays the prevailing gender practices in the Madhesi community that make women’s life devastated. The anthology highlights that existing gender norms promote inequality, violence and injustice against women. So, the study investigates how the gender roles are instituted and imposed to the females in the story “Janaani” in particular and in the Madhesi community in general. It scrutinizes the issues related to socially prescribed gender roles that bring in the life of Madhesi women. This paper assesses the factors that force the Madhesi women to subvert the scripted gender roles. To address these objectives, Judith Butler’s ideas on gender performativity, gender regulation and gender subversion are used. In Butler’s understanding of gender, the ‘performances of gender’ are enforced through the social script. She views that an individual’s gender is created by performing the script repetitively; however, the act of repetition creates the space for the individual to repeat the acts differently. Therefore, though a society constrains the individual in stereotyped gender roles, one seeks various possibilities within those constraints to break them. The selected story illuminates the prevailing gender stereotypes in the Madhesi community that act as a prime cause of the plight of Jamenty, the central character of “Janaani”. The paper concludes that since gender is an unstable entity which can be constituted by the individual differently, Jamenty, a representative female of the Madhesi community, subverts the socially imposed gender roles.